THE COMPLEX RELATIONSHIP BETWEEN SUFISM AND SHI‘ISM AS REFLECTED IN THE CONCEPT OF WALĀYAH - Wahyuddin Halim (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
This paper tries to examine the concept of walāyah in Sufism and Shi’ism. Walāyah is one of the most important principles in both Sufism and Shi’ism, occupying such a fundamental status within the whole structure of their metaphysical doctrines. Walāyah constitutes the idea on the necessary continuation of the spiritual authority of the Prophet Muhammad to particular authorities after the prophet’s death. Drawing from the same religious sources, both parties seem to develop the same concept of what constitutes walāyah and what the characteristics of those who deserve that spiritual authority, although they articulated the concept in different terminologies and functions.